Obesitas sentral berhubungan dengan toleransi glukosa terganggu pada remaja perempuan - Lucia Mawarti Dwi Astuti; Endy Paryanto Prawirohartono; Noormanto Noormanto; Madarina Julia (Jurnal Gizi Klinik Indonesia, 2012)
Background: Obesity in adolescents has become health problem in Indonesia. Central obesity is associated with insulin resistance.Theoretically, insulin resistance will cause impaired glucose tolerance (IGT) and could develop into type 2 diabetes.Objective: The aim of this study were to evaluate the difference in IGT prevalence between central and non central obesity and to identify the risk factors associated with IGT. Method: A cross sectional study was conducted at 3 private secondary schools in Yogyakarta and recruited 62 obese female students aged 12-18 years.The subjects were classified into central obesity (BMI/U> +2SD and waist circumference > p90) and non central obesity based on anthropometric data. Fasting glucose and 2 hours after loading were measured in all subjects. Differences in the proportion of IGT between the two groups was calculated by Chi-square test and risk factors associated with IGT were calculated by multivariate logistic regression with 95% confidence interval.Result: Of 62 subjects, 14 of them have IGT and the prevalence of IGT was significantly higher in the central obesity group compared to non central obesity group (11/31 vs 3/31, p=0.03). Central obesity was found to be the only risk factor of IGT (OR=4.6; 95%CI: 1.04 to 20.24). Twenty one of the subjects were found to have impaired fasting glucose (IFG) (34%) and one subject (1.6 %) had IFG+IGT. There were no differences in the proportion of IFG between central and non central obesity groups. Conclusion: The prevalence of IGT in female students with central obesity was higher compared to those with non central obesity. A female student with central obesity had 4.6-fold risk of having IGT compared to those with non central obesity.